Curved Dyonic Domain Walls in Four Dimensions - Bobby Eka Gunara (Department of Physics, Sebelas Maret University, 2016)
In this short paper we show the existence of solitonic solutions of four dimensional ungauged N=1 supergravity coupled to arbitrary vector and chiral multiplets whose Ricci scalar curvature is constant. The Ricci scalar of spacetimes indeed depends on the σ-model, namely the complex scalars and their first derivative. Then, we give two explicit models, namely static domain walls and static spherical symmetric black holes which are related to our previous works.